Kampus Mengajar sebagai Katalis Transformasi Pendidikan: Penguatan Literasi, Numerasi, dan Adaptasi Digital di SMK Kawasan Indonesia Timur: Penguatan Literasi, Numerasi, dan Adaptasi Digital di SMK Kawasan Indonesia Timur - Hariyanto, Hariyanto; Lasimpala, Satrio (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
The Kampus Mengajar (Teaching Campus) Program is one of the strategic policies under the Merdeka Belajar Kampus Merdeka (MBKM) framework, encouraging university students to contribute directly to improving the quality of primary and secondary education in Indonesia. This study aims to describe the implementation of the 8th Batch Kampus Mengajar Program in 2024 at SMK Negeri 3 Manado, North Sulawesi, as a representative vocational high school in Eastern Indonesia. A qualitative descriptive method was employed, with data collected through observation, in-depth interviews, and activity documentation. The results indicate that the program successfully implemented eleven work programs encompassing literacy strengthening (Financial Literacy, Health Literacy, Show and Tell, Literacy Festival), numeracy (Market Day, Magic Paper), digital adaptation (Canva Graphic Design Training, Digital Awareness Campaign), and school environment development programs (Library Revitalization, Herbal Corner, 3R). The Minimum Competency Assessment (AKM) demonstrated improvements in students’ literacy and numeracy from pre-test to post-test. The program also enhanced teachers’ creativity in utilizing learning technology. The study concludes that the Kampus Mengajar Program is effective as a catalyst for educational transformation in vocational high schools, particularly in Eastern Indonesia where educational resource constraints remain significant.